Chemistry of high-energy materials - Klapötke, Thomas M. (De Gruyter, 2011)
This graduate-level textbook treats the basic chemistry of high energy materials - primary and secondary explosives, propellants, rocket fuel and pyrotechnics - and provides a review of new research developments. Applications in both military and civil fields are discussed. The book also offers new insights into "green" chemistry requirements and strategies for military applications. This work should be of interest to advanced students in chemistry, materials science and engineering, as well as all those working in defense technology